Non-Specific Standardization Test for Areca Yaki Fruit Extract (Areca Vestiaria) - Nadine Natari; Herny Simbala; Erladys Rumondor (PHARMACON, 2023)
The chemical substances contained in the extracts of natural ingredients must be maintained in quality, so standardization is required. This study aims to prove that ethanol extract of Areca yaki Fruit (Areca Vestiaria) meets the non- specific parameters on the standardization of natural ingredients extract. Ethanol extract of Areca Yaki FruitÂ  is extracted using maceration method. The extracts obtained were tested for several non-specific parameters including desiccant shrinkage, moisture content, total ash content and acid insoluble ash content. The test results are compared with the standard parameters. Areca Yaki Fruit ethanol extract has a drying shrinkage of 0.027%, moisture content of 0.5242%, total ash content of 0.712% and 0.883%, and insoluble acid ash content of 0.048% and 0.056%. Areca Yaki Fruit ethanol extract meets the standard parameters, desiccant shrinkage, moisture content, total ash content, and insoluble acid ash content.